2015
DOI: 10.3109/0886022x.2014.1001304
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting eGFR 5-year post-deceased donor renal transplant: analysis and predictive model

Abstract: Aim: Long-term survival of renal allografts has improved over the last 20 years. However, less is known about current expectations for long-term allograft function as determined by estimated glomerular filtration rate (eGFR). The aim of this study was to investigate factors which affect graft function at 5 years' post-renal transplantation. The statistically significant factors were then used to construct a predictive model for expected eGFR at five years' post-transplant. Methods: We retrospectively reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Interestingly, Elbadri et al study have identified advanced donor age to be associated with low eGFR 5 years postrenal transplantation and advanced donor age to be a risk factor for delayed graft function (DGF), which is an independent predictor of late graft outcome and graft failure 14. We were also able to demonstrate that donor age to correlate with eGFR in our study in the patients group with transplantation >5 years (r=−0.4), but we did not experience higher USE stiffness results in Tx>5 years group with higher donor age (r=−0.3) 13.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Elbadri et al study have identified advanced donor age to be associated with low eGFR 5 years postrenal transplantation and advanced donor age to be a risk factor for delayed graft function (DGF), which is an independent predictor of late graft outcome and graft failure 14. We were also able to demonstrate that donor age to correlate with eGFR in our study in the patients group with transplantation >5 years (r=−0.4), but we did not experience higher USE stiffness results in Tx>5 years group with higher donor age (r=−0.3) 13.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing progress in transplantation medicine results in better success rates of organ transplantation and a prolongation of renal allografts' half-life. [3, 4] Despite the considerable progress of immunosuppressive regimens, acute rejection (AR) still remains a serious issue after KTx, which decreases patient and graft survival rates after its occurrence [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…These findings support our results. However, their overall donor age was much younger than our cohort (mean 36, range 21-47) and, they did not include HCV positive donors in their review [13].…”
Section: Discussionmentioning
confidence: 86%